2011
DOI: 10.1021/pr2006439
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Activity of HF3, a Snake Venom Metalloproteinase: Insights from the Proteomic Analysis of Mouse Skin and Blood Plasma

Abstract: Hemorrhage induced by snake venom metalloproteinases (SVMPs) is a complex phenomenon resulting in capillary disruption and blood extravasation. The mechanism of action of SVMPs has been investigated using various methodologies however the precise molecular events associated with microvessel disruption remains not fully understood. To gain insight into the hemorrhagic process, we analyzed the global effects of HF3, an extremely hemorrhagic SVMP from Bothrops jararaca, in the mouse skin and plasma. We report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 54 publications
3
55
1
6
Order By: Relevance
“…( table 1 ). Considering the fold change of 1.5 [Aragão et al, 2012a;Paes Leme et al, 2012], amylase has similar abundance among the samples and it was identified in a notable manner with the highest spectral counts, which means a high abundance of this protein in the acquired enamel pellicle independently of the enamel pretreatment. This result is consistent with earlier findings that indicated that amylase is one of the major components of pellicle [Hannig et al, 2004[Hannig et al, , 2005Siqueira et al, 2012b].…”
Section: Resultsmentioning
confidence: 95%
“…( table 1 ). Considering the fold change of 1.5 [Aragão et al, 2012a;Paes Leme et al, 2012], amylase has similar abundance among the samples and it was identified in a notable manner with the highest spectral counts, which means a high abundance of this protein in the acquired enamel pellicle independently of the enamel pretreatment. This result is consistent with earlier findings that indicated that amylase is one of the major components of pellicle [Hannig et al, 2004[Hannig et al, , 2005Siqueira et al, 2012b].…”
Section: Resultsmentioning
confidence: 95%
“…Differential protein spots were excised, reduced, alkylated and submitted to in-gel digestion with trypsin as described before [Paes Leme et al , 2012]. An aliquot (4.5 l) of the resulting peptide mixture was separated by C18 (75 m !…”
Section: Tryptic Digestion and Ms Analysismentioning
confidence: 99%
“…The whole extract of proteins (30 g) from each experimental condition was reduced, alkylated and digested with trypsin (Sigma) (1: 50) in 50 m M ammonium bicarbonate for 16 h at 37 ° C. The analysis was done as described before [Paes Leme et al , 2012], except that it was performed over 60 min with two runs for each sample. The resulting fragment spectra were searched as described above with decoy database with a maximum estimated false discovery rate of 1%.…”
Section: Tryptic Digestion and Ms Analysismentioning
confidence: 99%
“…Ainda que as cadeias alfa e beta fibrinogênio já tenham sido descritas como substratos do HF3 (Oliveira et al, 2010;Paes Leme et al, 2012), neste estudo a cadeia gama do fibrinogênio foi também detectada como um alvo desta metaloproteinase. Peptídeos oriundos da cadeia gama do fibrinogênio foram identificados como produto da atividade do HF3 no P(dep20) e P(enrq) (8)(9).…”
Section: Novos Substratos Proteínas Envolvidas Direta Ou Indiretamentunclassified
“…No estudo de Paes Leme et al (2012), foi verificado que a apolipoproteína A-II, o segundo maior componente do HDL, foi claramente degradada na pele hemorrágica. No presente estudo foi verificado que não somente a apolipoproteína A-II, como também outras proteínas desta classe (apolipoproteína A-I, A-IV, C-I, C-II, C-III, E, F e L1) foram detectadas como substrato do HF3 (Tabelas 2-9).…”
Section: Proteínas Envolvidas Na Inflamaçãounclassified